2023
DOI: 10.3389/fmicb.2023.1214845
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in PGPR-mediated resilience toward interactive effects of drought and salt stress in plants

Ahmad Al-Turki,
M. Murali,
Ayman F. Omar
et al.

Abstract: The present crisis at hand revolves around the need to enhance plant resilience to various environmental stresses, including abiotic and biotic stresses, to ensure sustainable agriculture and mitigate the impact of climate change on crop production. One such promising approach is the utilization of plant growth-promoting rhizobacteria (PGPR) to mediate plant resilience to these stresses. Plants are constantly exposed to various stress factors, such as drought, salinity, pathogens, and nutrient deficiencies, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 211 publications
(178 reference statements)
0
16
0
Order By: Relevance
“…In terms of soil quality, salt influences the composition of the microbial community in the soil and reduces biomass and microbial activity. Furthermore, under saline conditions, Na + exceeds K + transport channels, resulting in decreased and inhibited development of plants ( Al-Turki et al., 2023 ). Despite this, it has been demonstrated that co-application of PGPR and NPs in salty conditions induces salt tolerance and plant development, mostly through lowering Na + absorption and elevating the K + /Na + ratio.…”
Section: Soil Quality Enhancement: the Combined Power Of Pgpr And Nan...mentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of soil quality, salt influences the composition of the microbial community in the soil and reduces biomass and microbial activity. Furthermore, under saline conditions, Na + exceeds K + transport channels, resulting in decreased and inhibited development of plants ( Al-Turki et al., 2023 ). Despite this, it has been demonstrated that co-application of PGPR and NPs in salty conditions induces salt tolerance and plant development, mostly through lowering Na + absorption and elevating the K + /Na + ratio.…”
Section: Soil Quality Enhancement: the Combined Power Of Pgpr And Nan...mentioning
confidence: 99%
“…Using two endophytic bacteria, such as Burkholderia phytofirmans or Enterobacter sp., and NPs drastically reduced saline stress in crop plants by minimizing the uptake of xylem Na + content. On the contrary, combined application greatly enhanced the K + and K + /Na + ratio, reducing plant saline stress ( Kumawat et al., 2022 ; Al-Turki et al., 2023 ; Rajput et al., 2023b ). In the same demonstration, the sodium adsorption ratio and Na + in soil solution were reduced by the latter application to adsorption sites and desorption of K + by interactive combination.…”
Section: Soil Quality Enhancement: the Combined Power Of Pgpr And Nan...mentioning
confidence: 99%
See 2 more Smart Citations
“…Drought is a severe abiotic factor constraining plants and the human population due to decreased precipitation worldwide in the 21st century. Drought severity, water scarcity, and extreme temperatures alter soil moisture, affecting plant survival and crop productivity [ 2 , 3 ]. This stress results in stunted plant growth, lowers crop yield, hampers molecular metabolism, increases cellular reactive oxygen species (ROS), and affects morphological, physiological, and biochemical attributes that negatively impact plant health growth and crop productivity [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%